Aspergillus terreus, Penicillium sp. and Bacillus sp. isolated from mangrove soil having laccase and peroxidase role in depolymerization of polyethylene bags. (July 2022) - Mohy Eldin, Ahmed; Al-Sharnouby, Sohad Fouad Said; ElGabry, Khadiga Ibrahim Mohamed; Ramadan, Amal Ibrahim
Abstract: Low density polyethylene (LDPE) bags constituting major section in plastic wastes problem, were subjected to depolymerization study using microbial candidates isolated from mangrove soil. Three most promising microbial candidates were identified by rRNA gene sequencing analysis and uploaded in GenBank as Penicillium sp. [OM760513], Aspergillus terreus [OM760511] and Bacillus sp. [OM760515]. Incubation of the three candidates individually and in permutation and combination with LDPE bags in mineral salt medium broth (MSM) for 105 days revealed possible cooperative mechanism of microbial laccase and peroxidase in depolymerization of LDPE bag in an alternative manner. Weight loss by 24% and scan electron microscopy (SEM) examining surface of LDPE bag samples resulting from treatment with A. terreus OM760511 revealed its superiority. Attenuated Total Reflectance (ATR) Fourier Transform Infrared (FTIR) spectroscopy analysis revealed positive correlation between weight loss and changes in LDPE bag structure confirmed by increase in double bonds, shifting in absorption bands and decrease in T% parallel to decrease in both carbonyl index and crystallinity %. Graphical Abstract: ga1 Highlights: LDPE depolymerizers could be found among mangrove terrestrial microorganisms. Fungal laccases and peroxidases had essential role in plastic depolymerization. Polyethylene depolymerization confirmed by scan electron microscopy examination. Fourier Transform Infrared spectroscopy detected changes in polyethylene structure.